Research hotspots and trends of thoracic analgesia from 1994 to 2023: a bibliometric analysis - Meng, Yuxiang; Shi, Chenyang; Zhang, Hengrui; Ling, Zijie; Yuan, Sumin; Niu, Yang; Zhang, Li; Xu, Zhibiao; Liu, Yuyun; Liu, Su; Zhao, Linlin (Frontiers in Surgery, 2025)
PurposeThis study employs bibliometric analysis to comprehensively evaluate research trends in thoracic analgesia, identify evolving thematic priorities, and highlight emerging frontiers. The objective is to provide actionable insights to guide future investigations in this field.MethodsThe publications related to thoracic analgesia from the establishment of the Web of Science Core Collection (WOSCC) to 2023 were comprehensively searched. Utilizing CiteSpace (version 6.2.R4) software, this study conducted an in-depth analysis of the included publications, including disciplines, publication years, countries, institutions, authors, journals, cited references and keywords.ResultsA total of 3,895 articles related to thoracic analgesia were included in this study. Anesthesiology, surgery, respiratory system and cardiovascular system are the most active subjects in the study of thoracic analgesia. Since the first article was published in 1994, the number of articles related to thoracic analgesia has been on the rise. It is worth noting that the relevant literature mainly comes from developed countries, especially North America and Europe, of which the United States is far ahead. The analysis of institutions, authors and journals further reveals the important contributions made by the United States in the study of thoracic analgesia. In addition, the analysis of references on the number of citations showed that erector spinae plane block (ESPB), serratus anterior plane block (SAPB) and thoracic paravertebral block (TPVB) were the research hotspots in recent years. The analysis of key words also shows that Video-Assisted Thoracoscopic Surgery (VATS) and nerve block are the development trend in the field of thoracic surgery.ConclusionThis study highlights the research hotspots and trends in thoracic analgesia, nerve block-related techniques (e.g., ESPB, SAPB) emerged as dominant research hotspots. Future research hotspots will be more centered on the relationship between thoracic analgesia and nerve block.